2017
DOI: 10.3389/fphar.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ECV-Associated miRNAs as Potential Clinical Biomarkers in Early Stage HBV and HCV Induced Liver Fibrosis

Abstract: Introduction: Chronic hepatitis B (HBV) and C (HCV) virus infection is associated with the activation of hepatic stellate cells (HSCs) toward a myofibroblastic phenotype, resulting in excessive deposition of extracellular matrix, the development of liver fibrosis, and its progression toward cirrhosis. The gold standard for the detection and staging of liver fibrosis remains the liver biopsy, which is, however, associated with some mild and severe drawbacks. Other non-invasive techniques evade these drawbacks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 84 publications
1
40
0
1
Order By: Relevance
“…The miRNAs identified were involved in 100 signal transduction pathways, the majority of which affected liver fibrosis via the transforming growth factor-β/Smad, Wnt, mitogen-activated protein kinase, Janus kinase/signal transducers and activators of transcription and vascular endothelial growth factor pathways. A study conducted by Lambrecht et al ( 24 ) reported that miRNA-200b and miRNA-122 were significantly upregulated during early liver fibrosis and that miRNA-192, −92a and −150 were significantly downregulated in patients with HBV. Zheng et al ( 25 ) identified that levels of serum miR-125a-5p correlated with liver fibrosis and suggested that serum miR-125a-5p may be used as a non-invasive biomarker to monitor the progression of liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs identified were involved in 100 signal transduction pathways, the majority of which affected liver fibrosis via the transforming growth factor-β/Smad, Wnt, mitogen-activated protein kinase, Janus kinase/signal transducers and activators of transcription and vascular endothelial growth factor pathways. A study conducted by Lambrecht et al ( 24 ) reported that miRNA-200b and miRNA-122 were significantly upregulated during early liver fibrosis and that miRNA-192, −92a and −150 were significantly downregulated in patients with HBV. Zheng et al ( 25 ) identified that levels of serum miR-125a-5p correlated with liver fibrosis and suggested that serum miR-125a-5p may be used as a non-invasive biomarker to monitor the progression of liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…As attractive targets for novel diagnosis, circulating miRNAs have been proposed as biomarkers for different diseases and disorders including cancers, and infectious and inflammatory diseases [ 12 , 25 , 31 , 32 ]. Furthermore, circulating miRNAs have been proposed as having potential as predictors of fibrosis progression [ 1 , 14 , 26 , 27 , 30 ]. However, as there was limited information available, we aimed to determine the potential of measuring the levels of circulating miRNAs to trace the progression of hepatic fibrosis due to schistosomiasis.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study based on identification of miRNA levels, found different miRNAs in the EVs isolated from the plasma of the patients infected with HBV or HCV infection. Expression profile of miRNAs isolated from circulating vesicles showed reduced miR-192, miR-200b, miR-92a and miR-150a levels [32]. Thus, miRNAs expression levels can be correlated to early stage liver fibrosis identification.…”
Section: Exosomal Nucleic Acids As Cancer Biomarkersmentioning
confidence: 92%